2020
DOI: 10.3390/su13010097
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Agricultural Green Production Efficiency and Driving Factors of Urban Agglomerations in the Middle Reaches of the Yangtze River

Abstract: As one of the main grain-producing areas in China, urban agglomeration in the middle reaches of the Yangtze River plays an important role in the development of agricultural production for China’s grain supply. The existing studies about agricultural production efficiency lack of regional coordination analysis at both macro and micro levels, and only few studies consider the impact of agricultural production environment pollution and other undesirable outputs. Based on the input–output index system of agricultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 49 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…It is found that the type of basic ability of scientific and technological innovation indicators and transformation ability of scientific and technological achievements are the main indexes categories that affect grain output. This is highly consistent with the conclusion of most researchers that "agricultural science and technology innovation is the main driving force to promote agricultural development [42][43][44], and the transformation of scientific and technological achievements is an important factor affecting grain production efficiency [45][46][47][48]". It also shows that increasing the input of the investment of basic resources of scientific and technological innovation, effective allocation of resources, accelerating scientific and technological innovation and improving transformation rate of scientific and technological achievements are crucial for improving grain outputs and ensuring grain security.…”
Section: Discussionsupporting
confidence: 88%
“…It is found that the type of basic ability of scientific and technological innovation indicators and transformation ability of scientific and technological achievements are the main indexes categories that affect grain output. This is highly consistent with the conclusion of most researchers that "agricultural science and technology innovation is the main driving force to promote agricultural development [42][43][44], and the transformation of scientific and technological achievements is an important factor affecting grain production efficiency [45][46][47][48]". It also shows that increasing the input of the investment of basic resources of scientific and technological innovation, effective allocation of resources, accelerating scientific and technological innovation and improving transformation rate of scientific and technological achievements are crucial for improving grain outputs and ensuring grain security.…”
Section: Discussionsupporting
confidence: 88%
“…Some researchers used the entropy method to evaluate the level of agricultural green development in Anhui province ( 11 ), major grain-producing regions of China ( 12 ), Qinghai Province ( 13 ), and Jiangsu Province ( 14 ). Wang et al ( 15 ) based on the input-output index system of agricultural green production, Slacks-based model (SBM) was adopted to measure the agricultural green production efficiency of 31 prefecture-level cities in the middle reaches of the Yangtze River from 2008 to 2018, and the Tobit model of panel fixed effect was used to analyze the driving effect of external factors that affect the agricultural green production efficiency of urban agglomeration in the middle reaches of the Yangtze River. To evaluate the agricultural green development of China, Tu ( 16 ) used data envelopment analysis (DEA) research ideas and methods to calculate the agricultural green development index, analyzing the level of China's agricultural green development from both static and dynamic aspects, and based on variable coefficients semi-parametric estimation, analyzed the important determinants of agricultural green development and the influence of regional heterogeneity on agricultural green development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…507-516). Studies regarding sustainable development also include those by Wang et al (2021), who, using Data Envelopment Analysis (DEA), assessed the eco-efficiency of agricultural production. Thus, based on the review of literature, it can be concluded that an approach to evaluating and measuring competitiveness changed in time, which points to a need for continued research in order to present the complexity of this economic phenomenon from various perspectives (Roszko-Wójtowicz & Grzelak, 2020, pp.…”
Section: Literature Reviewmentioning
confidence: 99%